O estouro de bolhas especulativas recentes: Os casos dos Estados Unidos e do Jap\~ao - Ernani Teixeira Torres Filho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– This paper analyzes on a comparative basis the impact of the two major contemporary financial crises in Japan and in the United States. They were both the result of the burst of speculative bubbles that had allowed the high increase in the value of real estate and equity. The abrupt reversal of the financial markets led to the accumulation of huge losses not only by banks but also by non-financial corporations and households. In response, the private sector has been since then been systematically reducing its net debt and the level of investment, despite the recovery on the levels of profits and the long periods of interest rates at levels close to zero
Keywords: E44; F65; G15; N20; 330; financial globalization; speculative bubbles; balance-sheet recession